2007
DOI: 10.1093/brain/awm200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FGF-2 in neural progenitor cells enhances their potential for cellular brain repair in the rodent cortex

Abstract: Strategies to enhance the capacity of grafted stem/progenitors cells to generate multipotential, proliferative and migrating pools of cells in the postnatal brain could be crucial for structural repair after brain damage. We investigated whether the over-expression of basic fibroblast growth factor 2 (FGF-2) in neural progenitor cells (NPCs) could provide a robust source of migrating NPCs for tissue repair in the rat cerebral cortex. Using live imaging we provide direct evidence that FGF-2 over-expression sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 28 publications
6
66
0
6
Order By: Relevance
“…The lentivirus vector pRRL has been described elsewhere (47) and was kindly provided by Patrick Salomon, University of Geneva. The canine nectin-4 gene was synthesized in order to bear an additional N-terminal hemagglutinin (HA) tag (Eurofins).…”
Section: Methodsmentioning
confidence: 99%
“…The lentivirus vector pRRL has been described elsewhere (47) and was kindly provided by Patrick Salomon, University of Geneva. The canine nectin-4 gene was synthesized in order to bear an additional N-terminal hemagglutinin (HA) tag (Eurofins).…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that HIE disrupts the radiallyoriented pattern of RGC processes in the preterm-like rat brain, correlating in time with the appearance of reactive astrocytes (Sizonenko et al, 2007). However, it remains to be investigated if HIE accelerates the differentiation of RGC into astrocytes.…”
Section: Boosting the Endogenous Regenerative Capacity Of The Neonatamentioning
confidence: 99%
“…For instance, NT-3 (neurotrophin-3) overexpression in NSPC dramatically increases the neuronal differentiation of these cells when they are transplanted in the HI brain (Park et al, 2006b). FGF-2 overexpression can also enhance proliferation and migration of transplanted NSPC, increasing the number of donor NSPC-derived immature neurons in the HI brain (Dayer et al, 2007).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Elsayed et al 15 Jansen et al 16 Park et al 27 Imitola et al 23 Katsuragi et al 32 Katsuragi et al 33 Zheng et al 21 Meier et al 36 58 Park et al 22 Park et al 29 Ma et al 24 Dayer et al 30 BDNF = fator neurotrófico derivado do cérebro; BHK-GDNF = células renais de filhotes de hamster (BHK) transfectadas com DNA complementar de fator neurotrófico derivado de linhagem celular glial (GDNF); CPAM = células progenitoras adultas multipotentes; ChABC = condroitinase ABC; CTCUH = células-tronco de cordão umbilical humano; CTM = células-tronco mesenquimais; CTN = células-tronco neurais; CXCR4 = receptor de quimiocina CXC 4; FGF-2 = fator de crescimento de fibroblasto 2; GDNF = fator neurotrófico derivado de linhagem celular glial; HI = hipóxia-isquemia; ic = via intracerebral; ica = via intracardíaca; icv = via intracerebroventricular; ip = via intraperitoneal; iv = via intravenosa; NA = não avaliado; NGF = fator de crescimento neural; NT3 = neurotrofina -3; P = dia pós-natal; PGA = ácido poliglicólico; pT = pós-transplante; SDF-1 = fator derivado do estroma 1; T-PX = transplante no dia pós-natal X; SI = sem imunossupressão; TC = transplante contralateral; TI = transplante ipsilateral; VEH = veículo. * Animais tratados versus animais controle.…”
Section: Referênciaunclassified
“…Os autores sugerem que a produção da NT3 pelas CTN possa ter atuado de maneira autócrina e parácri-na, ligando-se às células adjacentes do tecido hospedeiro e estimulando a neurogênese endógena 22,29 . Outros estudos também têm demonstrado que CTN que superexpressam fatores tróficos específicos migram para a região lesada e formam nichos de células imaturas e proliferativas disponíveis para o reparo celular após HI 30 . Adicionalmente, identificou-se que o ambiente perivascular é fundamental para a manutenção dessas células em um estado ativo de imaturidade e proliferação 31 .…”
Section: Migração Celularunclassified